2017
DOI: 10.1080/03007995.2017.1358159
|View full text |Cite
|
Sign up to set email alerts
|

Non-guideline-recommended prescribing of proton pump inhibitors: implications for the future and reducing over usage

Abstract: Drs Godman and Fadare review the paper by Mares-Garcia and colleagues in Spain regarding the extent of non-guideline recommended prescribing (NGRP) of proton pump inhibitors (PPIs) in ambulatory care. NGRP of PPIs is an increasing public health concern given the implications of overuse of PPIs on infection rates, osteoporosis and chronic kidney disease as well as increasing polypharmacy rates. Costs are less of an issue especially where there are low prices for generic PPIs; the main focus is on improving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, there are concerns that long term use of PPIs can have patient safety issues (1,26). Safety concerns include increasing the rate of community acquired pneumonia, increasing the number of fragility fractures, as well as increasing the number of clostridium difficile infections (CDI) possibly due to changes in the gut microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are concerns that long term use of PPIs can have patient safety issues (1,26). Safety concerns include increasing the rate of community acquired pneumonia, increasing the number of fragility fractures, as well as increasing the number of clostridium difficile infections (CDI) possibly due to changes in the gut microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors increasing PPI use include their increased prescribing as prophylaxis for elderly patients with arthritis as well as those on multiple medications. In addition, patients are being prescribed PPIs alongside anticoagulant therapy to reduce potential GI bleeding and avoidable hospital admissions [83,[118][119][120][121]. However, these combined factors have resulted in the potential overuse of PPIs leading to possible complications [83,117,118].…”
Section: Potential Overuse Of Ppis and The Implicationsmentioning
confidence: 99%
“…In addition, patients are being prescribed PPIs alongside anticoagulant therapy to reduce potential GI bleeding and avoidable hospital admissions [83,[118][119][120][121]. However, these combined factors have resulted in the potential overuse of PPIs leading to possible complications [83,117,118]. Mares-Garcia et al found that over a third of patients over the age of 60 years had no obvious reason for being prescribed a PPI [116], which needs to be addressed.…”
Section: Potential Overuse Of Ppis and The Implicationsmentioning
confidence: 99%